Constraints on Early Paleozoic Deep‐Ocean Oxygen Concentrations From the Iron Geochemistry of the Bay of Islands Ophiolite. (5th July 2022) - Stolper, Daniel A.; Pu, Xiaofei; Lloyd, Max K.; Christensen, Nikolas I.; Bucholz, Claire E.; Lange, Rebecca A.
Abstract: The deep ocean is generally considered to have changed from anoxic in the Precambrian to oxygenated by the Late Paleozoic (∼420–400 Ma) due to changes in atmospheric oxygen concentrations. When the transition occurred, that is, in the Early Paleozoic or not until the Late Paleozoic, is less well constrained. To address this, we measured Fe 3+ /ΣFe of volcanic rocks, sheeted dykes, gabbros, and ultramafic rocks from the Early Paleozoic (∼485 Ma) Bay of Islands (BOI) ophiolite as a proxy for hydrothermal alteration in the presence or absence of O2 derived from deep marine fluids. Combining this data with previously published data from the BOI indicates that volcanic rocks are oxidized relative to intrusive crustal rocks (0.35 ± 0.02 vs. 0.19 ± 0.01, 1 standard error), which we interpret to indicate that the volcanic section was altered by marine‐derived fluids that contained some dissolved O2 . We compare our results directly to the Macquarie Island and Troodos ophiolites, drilled oceanic crust, previously compiled data for ophiolitic volcanic rocks, and newly compiled data for ophiolitic intrusive rocks. These comparisons show that the BOI volcanic (but not intrusive) rocks are oxidized relative to Precambrian equivalents, but are less oxidized relative to Late Paleozoic to modern equivalents. We interpret these results to indicate that the Early Paleozoic ocean contained dissolved O2, but at concentrations ∼2.4× lower than for the Late Paleozoic to today. Key Points: We report Fe 3+ /ΣFe in volcanic and intrusive crustal rocks and ultramafic rocks from the Early Paleozoic Bay of Islands (BOI) ophiolite Fe 3+ /ΣFe of the BOI volcanic rocks are elevated compared to Precambrian systems but lower than Late Paleozoic to modern systems This difference indicates deep‐ocean O2 levels in the Early Paleozoic were elevated compared to the Precambrian but lower than today